Giotto and his publics : three paradigms of patronage - Gardner, Julian (Bernard Berenson lectures on the Italian Renaissance., 2011)
"This probing analysis of three works by Giotto and the patrons who commissioned them goes far beyond the clichés of Giotto as the founding figure of Western painting. It traces the interactions between Franciscan friars and powerful bankers, illuminating the complex interplay between mercantile wealth and the iconography of poverty.